2004
DOI: 10.1364/ol.29.001191
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber humidity sensor based on evanescent-wave scattering

Abstract: An optical fiber humidity sensor has been devised using a porous sol-gel silica (PSGS) coating as a transducer. Evanescent wave scattering (EWS) in the PSGS coating. PSGS particles are highly hydrophilic and have a strong tendency to absorb water molecules from the surrounding environment. The absorbed water molecules form a thin layer on the inner surface of the pores inside the porous silica and enhance EWS, from which an indicatory signal can be obtained. The humidity sensor presented in this thesis has a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Previous research has shown different approaches of humidity sensors based on silica core fibre [1] [18] [19]. However, it is known that a silica core fibre may not be suitable for use in a harsh environment due to its fragility after removing the cladding.…”
Section: Studies By Wintermentioning
confidence: 99%
“…Previous research has shown different approaches of humidity sensors based on silica core fibre [1] [18] [19]. However, it is known that a silica core fibre may not be suitable for use in a harsh environment due to its fragility after removing the cladding.…”
Section: Studies By Wintermentioning
confidence: 99%
“…These sensors have various applications such as biosensing, chemical sensing, biochemical sensing, and humidity sensing [1][2][3][4][5][6][7]. For example, biosensor is used for biosensing, which is a process that detects the interactions of biological objects with a waveguide surface.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, humidity sensing is very important, especially in the control systems for industrial processes and for human comfort. In recent decades, various humidity sensors have been proposed and developed, which sense relative humidity (RH) in terms of resistance [4,5], capacitance [6], or refractive index (RI) [7]. Fiber-optic humidity sensor has some notable advantages over conventional electronic based humidity sensors, such as miniature dimensions, light weight, a potential for multi-parametric sensing, immunity to electromagnetic interference, water and corrosion resistance and radiation tolerance.…”
Section: Introductionmentioning
confidence: 99%